THE STUDENTSâ LANGUAGE LEARNING STRATEGIES IN READING AND SPEAKING - Azmi, Hidayat Al (Institut Agama Islam Negeri Imam Bonjol Padang, 2012)
Many types of learning strategies can be used by the language learners to make the learning process running well. However, in the doing the practice the students are identified have limited types of learning strategies and it makes them face many problems in learning. The aims of the study is to find the typical language learning strategies used by the English Department Students in speaking and reading in English. The result of the study showed that the level of the strategies used were still medium. Thus, the students of English Department are suggested to apply many strategies. it also hopes that the teachers are able to train sufficient strategy.